IISR Vajra – A new savour to Indian ginger - Prasath, D; Akshitha, H J; Sasikumar, B; Leela, N K; Aarthi, S; Aravind, Sharon (Indian Horticulture, 2023)
This article describes the new variety of ginger, IISR Vajra which has been released and recommended by AICRPS on Spices and Central Sub Committee on Crop Standards, Notification and Release of Varieties for Horticultural Crops for commercial cultivation in ginger growing tracts of Kerala, Karnataka, Odisha and West Bengal.